2003
DOI: 10.7589/0090-3558-39.4.824
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Revaccination of Pregnant Bison With Brucella Abortus Strain Rb51

Abstract: From December 1998 through February 1999, a study was conducted in a Brucellainfected bison herd to evaluate the safety of booster vaccination of adult bison (Bison bison) with 6ϫ10 9 colony forming units (CFU) of Brucella abortus strain RB51 (SRB51) that had previously been vaccinated as yearlings with 1ϫ10 10 CFU of SRB51. Abortions or other adverse effects were not observed after SRB51 booster vaccination. At 10 wk after adult vaccination, pregnant and nonpregnant bison (nϭ65) were randomly selected for bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…For inoculation methods ( Figure 6E ), subcutaneous vaccination is the most commonly used vaccination route ( Beckett and MacDiarmid, 1985 ; Elzer et al, 1998 ; Olsen and Holland, 2003 ; Ebrahimi et al, 2012 ; Singh et al, 2012 ). Conjunctival vaccination was associated with the highest abortion rate ( Zundel et al, 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…For inoculation methods ( Figure 6E ), subcutaneous vaccination is the most commonly used vaccination route ( Beckett and MacDiarmid, 1985 ; Elzer et al, 1998 ; Olsen and Holland, 2003 ; Ebrahimi et al, 2012 ; Singh et al, 2012 ). Conjunctival vaccination was associated with the highest abortion rate ( Zundel et al, 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…One study has found the incidence of abortion due to B. abortus challenge is significantly reduced in bison vaccinated with RB51 (1.2×10 10 –6.1×10 10 CFUs) when compared to unvaccinated controls (15% versus 62%) following conjunctival challenge with 3×10 7 CFUs 2308 (Olsen et al, 2003). Furthermore, revaccination of bison with RB51 did not cause abortion, but RB51 was recovered from tissue samples in 16.7% pregnant bison (Olsen and Holland, 2003). In a separate study, RB51 showed little efficacy in adult and calf bison despite repeated subcutaneous vaccinations with 1×10 7 –1×10 9 CFUs given as a primary immunization and boosted with 1×10 9 CFUs followed by a conjunctival challenge with 1×10 7 CFUs 2308 (Davis and Elzer, 2002).…”
Section: Live Vaccinesmentioning
confidence: 94%
“…Strain RB51 has also been shown to be generally effective as a vaccine in bison, generating host immune response, protection and ultimately prevention of abortion at doses of $10 10 CFUs (Roffe et al, 1999;Elzer et al, 1998;Davis and Elzer, 2002;Olsen et al, 1997Olsen et al, , 1998Olsen and Holland, 2003). This strain also has the inherent diagnostic advantage of not producing antibodies that interfere with standard serological field tests for brucellosis, limiting false positives observed from vaccination in field surveillance.…”
Section: Introductionmentioning
confidence: 93%